Petrogenesis of Havre Volcano in the Kermadec Arc: 2012 Eruption of a Chemically Homogeneous Rhyolite - Knafelc, J.; Gust, D.; Bryan, S. E.; Anderson, M.; Cathey, H. E. (Frontiers in Earth Science, 2022)
The 2012 Havre submarine eruption produced a 1.5 km3 bulk rock volume or 0.52 km3 dense rock equivalent volume of rhyolite emplaced as minor lava flows, a field of sunken seafloor pumice and a volumetrically dominant pumice raft. This moderately large volume of medium-K (1.4-1.6 wt.% K2O) rhyolite pumice is relatively chemically homogeneous (71.5-73.0 wt.% SiO2), and no trace element variation or cryptic zoning has been detected despite the textural diversity of pumice material. Radiogenic isotope ratios (87Sr/86Sr 0.703693-0.703744; 206Pb/204Pb 18.7648 – 18.7781; 208Pb/204Pb 38.587 – 38.605; 143Nd/144Nd 0.513001 – 0.513020) demonstrate the Havre rhyolite is sourced from mantle similar to regional eruptive products of the Kermadec arc volcanic front. Providing some further insight to the Havre magmatic system is an abundance of diverse volcanic rock fragments primarily embedded in the banded raft pumice. Embedded rock fragments represent a variety of fresh to hydrothermally altered lavas ranging in composition from basaltic to rhyolitic (50.6-72.3 wt. % SiO2) and are likely sourced from varying depths within the volcanic conduit during explosive fragmentation. The diverse volcanic embedded rock fragments therefore represent earlier erupted lavas that constructed Havre volcano and are snapshots of the petrogenetic history of Havre. Magnesian augite in basaltic to basaltic andesite embedded rock fragments have a similar compositional range (En55Fs12Wo33 to En39Fs26Wo35) to previously documented antecrystic clinopyroxene observed in 2012 rhyolite pumice raft. Here we offer one explanation to how this large-volume of chemically homogeneous crystal-poor rhyolite can be generated in an oceanic arc setting based on major and trace element petrogenetic models. Rhyolite-MELTs crystal fractionation models indicate the antecrystic mineral compositions within the Havre pumice of plagioclase (An 55-78), and magnesian augite (En53Fs10Wo37 to En40Fs26Wo34) are primary crystallizing phases that would crystallise in basaltic to andesitic melt compositions. Modelling indicates that the forerunner basaltic magma must be a relatively dry (~1 wt.% H20) low-K tholeiitic basalt in composition and would require ~78% crystallization at different pressures to ultimately generate the Havre 2012 rhyolite.